STRATEGI MANAJEMEN SUMBER DAYA MANUSIA BERBASIS INTELLIGENCE, ENGLIGHTENMENT, DAN ACHIEVEMENT DI ERA INDUSTRI 4.0 PADA PRODI ILMU FALAK - Akilah, Fahmiah; Basir, Fathur Rahman (ELFALAKY: Jurnal Ilmu Falak, 2023)
A sustainable human resource management strategy in the Astrology Study Program is an important aspect in facing the industrial era 4.0, so that the astronomy study program can remain relevant and competitive in producing graduates who are able to compete amidst the complex dynamics of Industry 4.0. The aim of this research is to analyze, design, and implement sustainable human resource management strategies in the astronomy sciences study program, so that they are able to maximize individual potential, improve the quality of teaching, and meet the demands of industry 4.0. This type of research is Library Research using a qualitative descriptive method approach that connects existing theories with the current descriptive reality of astronomy. Meanwhile, textual data was obtained from several literature sources and scientific articles related to this research. The conclusion of this research is that the implementation of a human resource management strategy based on intelligence, enlightenment and sustainable achievement in the astronomy sciences study program is able to increase the efficiency, effectiveness and competitiveness of institutions in facing the challenges of the industrial era 4.0. The implication of these findings is the need for commitment and investment from all related parties, including university leaders, lecturers, staff and other stakeholders, to implement sustainable human resource management strategies to achieve institutional goals and advance astronomy study programs in the industrial era 4.0 .